Endangered species, archaeology, and stable isotopes: Huemul (Hippocamelus bisulcus) isotopic ecology in central-western Patagonia (South America) - Barberena, Ramiro (2011)
The management and conservation of animal species should be based upon a long-term analysis that considers its geographical distribution and feeding patterns. The study of carbon and nitrogen stable isotopes on skeletal remains provides a quantitative approach to the paleodietary reconstructions and constitutes a potent tool for comparing behavioral aspects of the fauna. In this paper we present the first set of isotopic values for modern and archaeological samples of Huemul (Hippocamelus bisulcus) from the forests of Central-western Patagonia, Chile. Contrary to initial expectations, our analysis indicates that there is no evidence of an important incidence of the canopy effect on the δ13Ccollagen values, which we suggest is due to an ecological selection that drives the huemul to focus its predation on open sectors within the forest. On the other hand, a wide range of δ15Ncollagen values for huemul was verified. This could reflect the N impoverishment of the forest soils and provide an interesting ecological indicator. The long-term information offered by the archaeological record provides the necessary context for decision-making conducive towards the preservation of Hippocamelus bisulcus in Patagonia.